2015
DOI: 10.1088/0004-637x/807/2/149
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Observations of the Compton-Thick Nucleus of NGC 3393

Abstract: We present new NuSTAR and Chandra observations of NGC 3393, a galaxy reported to host the smallest separation dual AGN resolved in the X-rays. While past results suggested a 150 pc separation dual AGN, three times deeper Chandra imaging, combined with adaptive optics and radio imaging suggest a single, heavily obscured, radio-bright AGN. Using VLA and VLBA data, we find an AGN with a two-sided jet rather than a dual AGN and that the hard X-ray, UV, optical, NIR, and radio emission are all from a single point s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 72 publications
14
101
0
Order By: Relevance
“…Even if not intrinsically weak, the line detection is severely hampered by the low S/N. Throughsimulations, Koss et al (2015) found that the strong Fe Kα line (EW=1.11 keV) in a Compton-thick AGN NGC3933 (z=0.0125) can be detected at an S/N=3 by the 4Ms CDF-S only if z 0.2 < . This explains why the detection of neutral Fe Kα lines is inefficient in identifying Compton-thick AGNs in our high-z sample (Section 3.4.3).…”
Section: Distribution Of N H Excluding Compton-thick Sourcesmentioning
confidence: 99%
“…Even if not intrinsically weak, the line detection is severely hampered by the low S/N. Throughsimulations, Koss et al (2015) found that the strong Fe Kα line (EW=1.11 keV) in a Compton-thick AGN NGC3933 (z=0.0125) can be detected at an S/N=3 by the 4Ms CDF-S only if z 0.2 < . This explains why the detection of neutral Fe Kα lines is inefficient in identifying Compton-thick AGNs in our high-z sample (Section 3.4.3).…”
Section: Distribution Of N H Excluding Compton-thick Sourcesmentioning
confidence: 99%
“…Using simulations, Koss et al (2015) found that robust characterization of typical nearby CTAGN, such as NGC 3393, is only possible at relatively low redshifts of z 0.2 if one relies upon detection of the Fe Kα emission line and broad-band continuum for spectral modelling.…”
Section: Implications For Identifying Ctagn At a Low X-ray Signal To mentioning
confidence: 99%
“…Dominance of the R component in the hard X-ray band is not favored either, as the EW of Fe Kα is relatively low. Instead, IRAS 09104+4109 resembles heavily obscured AGNs in the nearby universe, in which both T and R components contribute to the X-ray spectrum in the NuSTAR band (e.g., Puccetti et al 2014;Koss et al 2015;M. Baloković et al 2016, in preparation).…”
Section: The X-ray Datamentioning
confidence: 99%